A Grounding System Model Directly in Time-Domain - Mendes Seixas, Claudiner; Kurokawa, Sergio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This work presents a technique for electrical grounding system representation, directly in the time domain. It is based on the theory of least squares and starts from harmonic grounding impedance, representing it by discrete element circuits (resistors, capacitors and inductors) associated in series-parallel. From the impedance can be determined the transient ground voltage due to current impulse (lightning) applied, which is one of the quantities of greatest interest in the grounding studies. The advantage of using models developed directly in the time domain is that they can be easily inserted into conventional simulation software, such as the Alternative Transient Program (ATP), Electromagnetic Transient Program (EMTP) and Orcad (PSPICE). To determine the harmonic grounding impedance («view» from the point struck by lightning), was used as a tool a model based on the theory of transmission lines considering distributed parameters, but could be used any other model, independent of the simplifications and boundary conditions used in their representation, such as the electromagnetic model. The validation of this method was made by comparing the results of this work (for vertical rod and horizontal electrode) with another obtained and already validated through experimental results by one renowned research group in the electrical grounding area, achieving good agreement.
Keywords: Electrical grounding; electromagnetic transients; frequency domain; ground impedance; lightning; modeling; soil resistivity; time domain